1997
DOI: 10.1177/073428299701500405
|View full text |Cite
|
Sign up to set email alerts
|

Phonological Awareness Skills in Children: Examining Performance across Tasks and Ages

Abstract: This study examined the performances of 171 children in kindergarten through second grade on 11 tasks of phonological awareness. The purpose was to assess phonological awareness skill acquisition across age and type of task. Results provided support for an ordering of tasks by difficulty, or age of mastery, as follows: rhyme, alliteration, blending, segmentation, manipulation. Performance on all of the tasks demonstrated rapid growth in 6-year-old children (first grade), and most tasks were mastered (90% corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
5

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 12 publications
1
11
0
5
Order By: Relevance
“…As children progress through the educational system, adequate and robust word reading ability by all children is the foundation for more advanced ability in reading comprehension (Kahmi, 2007;Perfetti, 1985;Perfetti & Hagoboam, 1975). Careful and systematic assessment of phonological awareness across a developmental hierarchy of skills, including skill in rhyming, blending segmenting, and phoneme manipulation (Chafouleas, Lewandowski, Smith, & Blachman, 1997;Gillon, 2004), can and should lead to appropriate clinical and classroom intervention to help support the development of robust word analysis ability in reading.…”
Section: Conclusion Clinical Implications and Future Directions Formentioning
confidence: 99%
“…As children progress through the educational system, adequate and robust word reading ability by all children is the foundation for more advanced ability in reading comprehension (Kahmi, 2007;Perfetti, 1985;Perfetti & Hagoboam, 1975). Careful and systematic assessment of phonological awareness across a developmental hierarchy of skills, including skill in rhyming, blending segmenting, and phoneme manipulation (Chafouleas, Lewandowski, Smith, & Blachman, 1997;Gillon, 2004), can and should lead to appropriate clinical and classroom intervention to help support the development of robust word analysis ability in reading.…”
Section: Conclusion Clinical Implications and Future Directions Formentioning
confidence: 99%
“…Kindergarten children are only beginning the process of learning to read. Not only does this study not examine how these phonological measures relate to reading in more advanced readers, but previous research (e.g., Ball, 1993;Chafouleas, Lewandowski, Smith, & Blachman, 1997) has demonstrated that phonological tasks vary in difficulty and that the age which these tasks are mastered varies. As children develop, the relationships among predictor variables and reading may change.…”
Section: Discussionmentioning
confidence: 97%
“…Az olvasni tanulás ráépül a szavak hangszerkezetére, majd egyidejűleg serkenti a szavak hangszerkezetének megértését, azaz a fonológiai tudatosság fejlődését. Az olvasás és a fonológiai tudatosság kölcsönösen erősíti egymást (Chafouleas, Lewandowsic, Smith és Blachman, 1997), közöttük erős reciprok kapcsolati kölcsönhatás tapasztalható (Perfetti, Beck, Bell és Hughes, 1987;Wagner és Torgesen, 1987;Wimmer, Landerl, Linortner és Hummer, 1991). A kezdő olvasónak először meg kell tanulnia, hogy hogyan kell dekódolnia a nyomtatott szót, mielőtt megértené az írott szöveget (Pratt és Brady, 1988;Wagner és Torgesen, 1987).…”
Section: Elméletek a Fonológiai Tudatosság éS Az Olvasás Kapcsolatábanunclassified